Clinical and epidemiologic characterization of non-infectious uveitis in a university hospital in Paraguay - Figueredo Rojas, Abel Esteban; Vera-Duarte, Guillermo Raul; Delgado-Herrera , Claudia Leticia; Arrúa Caballero, Martin Fernando; González Sanabria, Luis (Medicina Clínica y Social, 2024)
Objective: To determine the clinical and epidemiological characteristics of patients with noninfectious uveitis at a university hospital in Paraguay. Methodology: An observational, descriptive, cross-sectional, retrospective study was performed. Consecutive patients who attended the Ophthalmology Service of the Hospital de Clínicas from January 2020 to October 2021 and who were diagnosed with non-infectious uveitis were included. The variables studied were sex, age, origin, reason for consultation, anatomical classification, clinical course, systemic and ocular associations, and bilaterality. Results: A total of 78 medical records of patients meeting the inclusion and exclusion criteria were analyzed. Of the patients, 66.7% were female and 42 (53.8%) were from the Central Department. The anterior anatomical location of uveitis was the most frequent (53.9%), followed in decreasing order by panuveitis, posterior uveitis, and intermediate uveitis. Regarding anterior uveitis, 24 patients (57.1%) had unilateral uveitis, 40 (95.2%) were non-granulomatous, 19 (45.2%) presented an acute clinical course, the most frequent reason for consultation was "red and painful eye" with 15 patients (35.7%), the most frequent systemic association was HLA- B27+ in 16 patients (38.1%). As for panuveitis, 13 patients (50%) were associated with Vogt-Koyanagi-Harada syndrome, and of the latter, two patients were related to rheumatoid arthritis. Conclusion: The clinical and epidemiological patterns observed in this study were largely consistent with those reported in the literature. Notably, the most frequent associations differed from those reported in the literature: HLA-B27+ for anterior uveitis, rheumatoid arthritis for posterior uveitis, and a significant percentage of Vogt-Koyanagi-Harada syndrome among panuveitis cases.
Keywords: Uveitis; Non-infectius uveitis; clinical characterization; epidemiology